Killing method affects the browning and the quality of the protein fraction of Black Soldier Fly (Hermetia illucens) prepupae: a metabolomics and proteomic insight. (January 2019) - Leni, Giulia; Caligiani, Augusta; Sforza, Stefano
Abstract: Insects are being explored as novel protein sources in order to overcome the future food demands connected to world growing population. Insects for food/feed uses are currently slowly killed through freezing by most insect rearing companies, and typically, enzymatic browning takes place in the insect proteins fractions. However, very little is known about the influence of these enzymatic reactions on the protein physical, chemical, nutritional and technological properties. In this work a metabolomics and proteomic study was conducted on Black Soldier Fly ( Hermetia illucens) prepupae, killed by two different methods: freezing (commonly used), and blanching (with the aim to inhibit the enzymatic activities). Proton nuclear magnetic resonance ( 1 H NMR) metabolomics demonstrated that slow killing method by freezing, compared with blanching, elicits the activation of several enzymatic pathways, among them melanisation with tyrosine consumption, energetic metabolism and lipolysis. These metabolic changes have an impact also on protein nutritional quality, with a loss of cysteine and lysine, likely involved in the process of melanisation and enzymatic browning. A strong effect was also observed on protein extractability: proteins from prepupae killed by blanching were found to be more extractable in milder conditions by chemical methods, and more prone to enzymatic digestion (97% of proteins released in solution upon proteolysis) than proteins from prepupae killed by freezing. All these data indicate that killing by blanching inhibits the browning reaction and other enzymatic changes occurring during slow killing by freezing, increasing the extractability of proteins in aqueous solutions, avoiding essential amino acid loss, and improving enzymatic digestibility. Graphical abstract: Unlabelled Image Highlights: Blanching and freezing were explored as killing methods for black soldier fly prepupae. Blanching reduced the browning of proteins caused by phenol oxidase. 1 H NMR metabolomics proved that blanching inactivates several enzymatic pathways which are active in frozen preupae. Proteomic analysis demonstrated modification on amino acids profile and protein quality upon freezing. Blanching improved protein extractability and susceptibility to enzymatic digestion.